The Impact of Robot Adoption on Global Sourcing - Akin A. Cilekoglu; Rosina Moreno; Raul Ramos (Institute of Labor Economics (IZA), 2021)
This paper studies the impact of robot adoption on firms' global sourcing activities. Using a rich panel dataset of Spanish manufacturing firms, we show that robot adopting firms increased their intermediate input purchases from foreign and domestic suppliers between 2006 and 2016. The effects of robots differ across sourcing strategies: the highest in foreign outsourcing and the lowest in foreign vertical integration. We find that robot adopters fragment their production further by reducing the concentration of purchases from suppliers and the increase in intermediate input purchases is related to quality upgrading to a certain extent. Marginal treatment effects estimates suggest that responses to adoption are heterogeneous: higher probability of adoption intensifies the effects on outsourcing and weakens the effects on vertical integration. In contrast to rising concerns over reshoring, our findings suggest that robots have yet promoted trade in intermediate inputs.
Keywords: F14; F23; L23; 330; robots; reshoring; trade; production fragmentation